Effect of estradiol benzoate microinjection into the median raphe nucleus on contextual conditioning - Andrade, Telma Gonçalves Carneiro Spera de [UNESP]; Avanzi, Viviane [UNESP]; Graeff, Frederico G. (Elsevier B.V., 2009)
Estrogen deficiency has been associated with stress, anxiety and depression. Estrogen receptors have been identified in the median raphe nucleus (MRN). This structure is the main source of serotonergic projections to the hippocampus, a forebrain area implicated in the regulation of defensive responses and in the resistance to chronic stress. There is reported evidence indicating that estrogen modulates 5-HT(1A) receptor function. In the MRN, somatodendritic 5-HT(1A) receptors control the activity of serotonergic neurones by negative feedback. The present study has evaluated the effect of intra-MRN injection of estradiol benzoate (EB, 600 or 1200 ng/0.2 mu l) on the performance of ovariectormized rats submitted to contextual conditioning. Additionally, the same treatment was given after intra-MRN injection of Way 100635 (100 ng/0.2 mu l). a 5-HT(1A) receptor antagonist. Both doses of EB decreased freezing and increased rearing, indicating an anxiolytic effect. Pretreatment with Way 100635 antagonized the anxiolytic effect of estradiol. on the basis of these results, it may be suggested that estrogens modulate anxiety by acting on 5-HT(1A) receptors localized in the MRN. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Median raphe nucleus; Estradiol; Anxiety; Contextual conditioning; Serotonin; 5-HT(1A) receptor